TiO2 (at) Ag / Ti-MOF functional material and preparation method thereof

By constructing Ag-MOF on TiO2 photocatalytic material and forming a core-shell structure, the problems of low light utilization rate and insufficient reactive sites of TiO2 photocatalytic materials are solved, and efficient photocatalytic bactericidal effect is achieved.

CN119563648AActive Publication Date: 2025-03-07UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411496114.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The low light utilization rate and insufficient reactive sites of TiO2 photocatalytic materials lead to limited energy waste and application expansion.

Method used

Using TiO2@Ag/Ti-MOF functional material, Ag-MOF is constructed on the Ti-MOF skeleton to achieve controllable sustained release of Ag ions, and a core-shell structure with TiO2 as the core and Ti-MOF replaced with Ag is formed to enhance the bactericidal performance.

Benefits of technology

The photocatalytic sterilization efficiency is improved, and the long-term effective sterilization effect is achieved. The photogenerated electrons are efficiently captured through the core-shell structure, enhancing the sterilization performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563648A_ABST
    Figure CN119563648A_ABST
Patent Text Reader

Abstract

A photocatalytic sterilization technology is a technology for killing microorganisms such as bacteria, viruses and the like by utilizing active substances generated by a specific material under an illumination condition. The technology mainly depends on the performance of photocatalytic materials, especially semiconductor materials such as titanium dioxide (TiO2). When the photocatalyst is irradiated by light with a specific wavelength, electrons in the material are transited from a valence band to a conduction band to form electron-hole pairs. The electrons and holes have very high chemical activity, can react with water or oxygen to generate free radicals with strong oxidizing capacity, and can destroy cell walls or cell membranes of microorganisms to cause leakage of substances in cells, so that the sterilization effect is achieved. The invention provides a TiO2 (at) Ag / Ti-MOF functional material aiming at the problems of low light utilization rate and insufficient reaction active sites of a TiO2 photocatalytic material. According to the TiO2 (at) Ag / Ti-MOF functional material, Ag-MOF is constructed on the basis of a Ti-MOF framework, controllable slow release of Ag ions is achieved, and the long-time effective sterilization effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalytic sterilization materials, and in particular to a TiO2@Ag / Ti-MOF functional material and a preparation method thereof. Background Art

[0002] Photocatalytic sterilization technology is a technology that converts light energy into chemical energy. When light irradiates on a semiconductor photocatalytic material, if the energy of the irradiated light is greater than the excitation energy of the photocatalytic material, the electrons (e - ) will be excited to the conduction band (CB) to form photoexcited electrons, while leaving holes (h + ). Subsequently, the photogenerated electron and hole pairs will migrate to the surface of the semiconductor photocatalytic material to participate in reduction and oxidation reactions. The active free radicals ROS (•OH, •O2 - , •HO2) can kill bacterial pathogens by attacking bacterial cell membranes, proteins, DNA and other biological macromolecules, making bacteria inactive.

[0003] As the earliest and most widely studied photocatalytic antibacterial material, TiO2 has a series of advantages such as strong photocatalytic bactericidal activity, long antibacterial time, and high human affinity. It is an excellent bactericidal material. As an N-type semiconductor, TiO2 is a natural photocatalytic bactericidal material. Studies have shown that under the irradiation of ultraviolet light, TiO2 will form ROS with strong oxidizing properties on its surface. These ROS will spontaneously attack bacterial phospholipids, proteins, nucleic acids and other biological macromolecules. The bacterial cell membrane, cytoplasm and organelles will be destroyed in turn, thereby achieving long-lasting and efficient harmless treatment of bacteria. However, the low light utilization rate and insufficient reaction active sites of TiO2 photocatalytic materials have led to great energy waste, limiting the expansion of the application of this type of material. Summary of the invention

[0004] Based on the above content, in order to solve the problems of low light utilization rate and insufficient reaction active sites of TiO2 photocatalytic materials, the present invention proposes a TiO2@Ag / Ti-MOF functional material and its preparation method. TiO2@Ag / Ti-MOF functional material is based on the Ti-MOF skeleton to construct Ag-MOF, realizes the controlled slow release of Ag ions, and has a long-term and effective bactericidal effect.

[0005] One of the technical solutions of the present invention is to provide a TiO2@Ag / Ti-MOF functional material, which has a core-shell structure, wherein the core is TiO2 and the shell is a silver-substituted Ti-MOF structure. There is a tight interface between the core and the shell, which can efficiently capture the photogenerated electrons generated by TiO2 after illumination, and the silver ions in the MOF are reduced to silver atoms, thereby enhancing its bactericidal performance.

[0006] The second technical solution of the present invention is to provide a method for preparing TiO2@Ag / Ti-MOF functional material, which specifically comprises the following steps: (1) Preparation of Ti-MOF with Ti vacancies by microwave hydrothermal method; (2) Filling the Ti vacancies on the surface with silver ions to form a Ti vacancy-MOF@Ag / Ti-MOF structure; (3) The Ti-MOF@Ag / Ti-MOF structure is heated to form a TiO2@Ag / Ti-MOF structure.

[0007] Furthermore, the Ti-MOF with Ti vacancies is prepared by the following method: 1) Prepare 2-aminoterephthalic acid in N, N-dimethylimidazole (DMF) at a concentration of 0.2-0.3 mmol / mL as solution A; 2) dissolving tetrabutyl titanate in anhydrous methanol and mixing them evenly to obtain solution B; the volume ratio of the tetrabutyl titanate to anhydrous methanol is 1:(22-28); 3) Mix solution A and solution B in a molar ratio of tetrabutyl titanate and 2-aminoterephthalic acid of 1: (0.2-5); after mixing evenly, transfer to a microwave oven with a microwave power of 600 W and a heating time of 2 hours, and dry the precipitate to obtain a Ti-MOF with Ti vacancies.

[0008] Furthermore, the Ti vacancy-MOF@Ag / Ti-MOF structure is prepared by the following method: dispersing Ti-MOF with Ti vacancies in a silver ammonia solution, transferring it to a closed container, and filling the container with the solution to more than 2 / 3 of the volume; reacting at 80°C for 240 to 300 minutes to obtain a Ti vacancy-MOF@Ag / Ti-MOF structure.

[0009] Furthermore, the concentration of the silver ammonia solution is 1-3 mol / L; the mass fraction of the Ti-MOF with Ti vacancies in the solution is 14-35%.

[0010] Furthermore, in step 3 of the preparation method of the TiO2@Ag / Ti-MOF functional material, the heating of the Ti-MOF@Ag / Ti-MOF structure is to transfer the Ti-MOF@Ag / Ti-MOF to a tubular furnace and perform a heat treatment at 200-300°C in an air environment to obtain the TiO2@Ag / Ti-MOF structure.

[0011] In the process of preparing Ti-MOF with Ti vacancies, 2-aminoterephthalate was used as a ligand and N, N-dimethylimidazole was used as a solvent. A Ti-MOF with Ti vacancies was formed by microwave hydrothermal method. 4+The ions use the octahedral configuration of multiple coordination sites to connect the two unit fragments into a chain through the oxygen atoms on the carboxyl group. The Ti-based material forms a metal-ligand bond and a rigid skeleton, showing good redox activity, good structural stability and coordination diversity. The high-frequency electromagnetic energy of microwaves has penetrating properties, causing molecules to vibrate and rub, efficiently heating, reducing the activation energy barrier, accelerating the crystallization rate, thereby reducing the sample grain size and improving uniformity. Moreover, microwave heating not only provides energy to accelerate the reaction, but may also promote structural reconstruction or instability due to the local high temperature and pressure environment, indirectly leading to the formation of Ti vacancies.

[0012] Then, silver ions are used to fill the Ti vacancies on the surface. This step is carried out in a closed container. During the reaction, the vapor pressure in the solution increases, which effectively promotes the diffusion and penetration of silver ions in the silver ammonia solution into the interior of the Ti-MOF. The high temperature and high pressure environment of 80 °C can reduce the resistance of gas molecules in the MOF pores, making it easier for silver ions to enter and contact the vacancies, thereby filling the Ti vacancies on the surface. At the same time, the silver ions are reduced to silver atoms and then "fixed" on the titanium vacancies. This reduction process, combined with the ammonia complex in the silver ammonia solution, can effectively promote the deposition and stabilization of silver.

[0013] During the heating process of the Ti-MOF@Ag / Ti-MOF structure, the outer layer of Ag / Ti-MOF maintains its original structure due to its good crystallinity, while the vacancies in the inner layer are not filled and have defects, and TiO2 will be formed under hot air, eventually forming a core-shell structure with Ag / Ti-MOF as the shell and TiO2 as the core.

[0014] The beneficial effects of the present invention are: Ag-MOF is constructed based on the Ti-MOF framework, and the controlled slow release of Ag ions is achieved, which has a long-term and effective bactericidal effect. Furthermore, a composite structure with Ag-MOF as the shell and TiO2 as the core is constructed, and there is a close interface between the core and the shell, which can efficiently capture the photogenerated electrons generated by TiO2 after illumination, and the silver ions in MOF are reduced to silver atoms, thereby enhancing the bactericidal performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 TEM images of Ti-MOF and Example 1; Figure 2 is the EDS image of Example 1; Figure 3 XRD spectra of Ti-MOF and Example 1; Figure 4 FT-IR images of Ti-MOF and Example 1; Figure 5 is the XPS spectrum of each element orbital in Ti-MOF and the material of Example 1; Figure 6 The following are the bactericidal effect diagrams of TiO2, Ti-MOF, Ti-MOF@Ag / Ti-MOF and TiO2@Ag / Ti-MOF. DETAILED DESCRIPTION

[0016] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0017] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0018] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0019] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0020] Example 1 1) Prepare 2-aminoterephthalic acid in N, N-dimethylimidazole (DMF) at a concentration of 0.2 mmol / mL as solution A; 2) dissolving tetrabutyl titanate in anhydrous methanol and mixing them evenly to obtain solution B; the volume ratio of the tetrabutyl titanate to anhydrous methanol is 1:22; 3) Solution A and solution B were mixed in a molar ratio of tetrabutyl titanate to 2-aminoterephthalic acid of 1:0.2; after being mixed evenly, the mixture was transferred to a microwave oven, the microwave power was set to 600 W, the heating time was set to 2 hours, and the precipitate was dried to obtain a Ti-MOF with Ti vacancies; 4) Disperse the Ti-MOF with Ti vacancies in a 1 mol / L silver ammonia solution, where the mass fraction of the Ti-MOF with Ti vacancies in the solution is 14%. Transfer the mixed solution to a sealed container, and fill the container with the solution to more than 2 / 3 of its volume; 5) React at 80 °C for 240 min to obtain a Ti vacancy-MOF@Ag / Ti-MOF structure; 6) The Ti-MOF@Ag / Ti-MOF was transferred to a tube furnace and heat treated at 200 °C in an air environment to obtain a TiO2@Ag / Ti-MOF structure.

[0021] The obtained product TiO2@Ag / Ti-MOF was then characterized.

[0022] Figure 1 a and Figure 1 b are TEM images of Ti-MOF and Ti-MOF@Ag / Ti-MOF materials, respectively. It can be observed that the Ti-MOF material has a solid structure inside and a smooth surface. Figure 1 c is the TEM image of the TiO2@Ag / Ti-MOF composite material. It can be seen from the image that compared with the Ti-MOF material, the smooth surface of the TiO2@Ag / Ti-MOF composite material is transformed into a rougher surface with fine microcrystalline particles, and the size is significantly reduced. Figure 1 d is the HRTEM image of TiO2@Ag / Ti-MOF. It was measured that TiO2@Ag / Ti-MOF has a (200) crystal plane of the Ag nanoparticle lattice, and its interplanar spacing is 2.05 Å.

[0023] Figure 2 is the EDS image of TiO2@Ag / Ti-MOF. Figures dg respectively represent the distribution of C, O, Ti and Ag, proving that C, O, Ti and Ag elements are uniformly distributed in the TiO2@Ag / Ti-MOF functional material, among which C, O and Ti elements are the basic elements of Ti-MOF material, and Ag element is nano-Ag particles loaded by microwave solvothermal method.

[0024] according to Figure 3 From the XRD spectrum, it can be seen that compared with Ti-MOF, the TiO2@Ag / Ti-MOF composite material retains the main peak of Ti-MOF at about 6.5° and the continuous peaks near 20°. The peaks at 25.6°, 48.7°, 63.1° and 63.7° belong to the (101) crystal plane, (200) crystal plane, (213) crystal plane and (204) crystal plane of TiO2 rutile phase, respectively, indicating that the TiO2@Ag / Ti-MOF composite material has the TiO2 rutile phase and retains part of the Ti-MOF crystal structure.

[0025] Figure 4 The FT-IR images show that there are certain organic skeleton components in the TiO2@Ag / Ti-MOF composite material. Figure 4 As shown in the TiO2 material spectrum, 3450 cm -1 and 1620 cm -1 The absorption peaks at 3400 cm in the spectrum are caused by the stretching vibration of the hydroxyl group (-OH) of water and the bending vibration of the HOH bond, which is due to the absorption of water by the material when exposed to air.-1 The broad absorption peak at 2925 cm-1 is produced by the stretching vibration of the hydroxyl (-OH) and amino (-NH2) groups of water. -1 The absorption peak at 1640 cm -1 and 1420 cm -1 The infrared absorption peak at 1080 cm is caused by the asymmetric and symmetric stretching vibration of the OC=O bond. -1 The absorption peak at is due to the vibration of CO bond. From the above conclusions, it can be seen that there is an organic skeleton component in the TiO2@Ag / Ti-MOF composite material, which proves the successful synthesis of TiO2@Ag / Ti-MOF material.

[0026] Figure 5 XPS spectra of the orbitals of each element in Ti-MOF and TiO2@Ag / Ti-MOF materials are used to prove the structure of TiO2@Ag / Ti-MOF materials and the changes in the types of elements and their coordination environments. Figure 5 a~d are the XPS spectra of C 1s, O1s, N 1s and Ti 2p in Ti-MOF materials, respectively. Figure 5 The C 1s high-resolution energy spectrum in a can be fitted into four convolution peaks at 284.8 eV, 285.6 eV, 286.2 eV and 288.9 eV, corresponding to the peaks of CC / CH, CN, C=C and OC=C, respectively. Figure 5 The O 1s peak in (b) can be fitted into peaks with binding energies of 530.1 eV, 532.0 eV, and 532.4 eV, which correspond to the characteristic peaks corresponding to Ti-O, C=O, and -OH hydroxyl groups, respectively. Figure 5 The N 1s peak in c can be separated into peaks with binding energies of 399.5 eV and 402.5 eV, corresponding to -NH2 and -N += / -NH +- Characteristic peak. Figure 4 The peaks of 458.8 eV and 464.5 eV in d belong to the peaks formed by the electron spin separation in Ti 2p orbital. Figure 5 f~i are the XPS spectra of C 1s, O 1s, N 1s, Ti 2p and Ag 3d in TiO2@Ag / Ti-MOF materials. Compared with the peaks corresponding to each element in Ti-MOF materials, Figure 4 The binding energies of the characteristic peaks of CC / CH, CN and C=C in the C 1s spectrum of e are 284.6 eV, 285.0 eV and 285.9 eV, which decrease by 0.2 eV, 0.6 eV and 0.3 eV respectively. Only the binding energy of OC=C increases slightly by 0.1 eV to 289.0 eV. Figure 5The binding energies of the characteristic peaks in O 1s corresponding to Ti-O, C=O and -OH hydroxyl groups are 529.9 eV, 530.5 eV and 532.0 eV, respectively, which decrease by 0.5 eV, 1.5 eV and 0.4 eV, respectively. Figure 5 N1s in g corresponds to -NH2 and -N += / -NH +- The characteristic peak binding energies are 399.6 eV and 401.7 eV, which increase by 0.1 eV and decrease by 0.8 eV, respectively. Figure 5 The binding energies of Ti 2p orbitals in h are 459.0 eV and 464.8 eV, respectively, which increase by 0.2 eV and 0.3 eV. Figure 5 The difference in binding energy of Ag3d orbit in i is 6.0 eV, which proves the successful loading of single-element Ag nanoparticles in TiO2@Ag / Ti-MOF material.

[0027] In summary, it can be proved that the preparation method of the present invention can successfully synthesize a photocatalytic functional material with a core-shell structure having TiO2 as the core and Ag-substituted Ti-MOF as the shell.

[0028] In order to test the photocatalytic bactericidal performance of the prepared materials, Gram-negative brevis Escherichia coli (E.coil) was selected as the test bacteria, photocatalytic bactericidal drugs (TiO2, Ti-MOF, Ti-MOF@Ag / Ti-MOF or TiO2@Ag / Ti-MOF) 50 μg / mL, E. coli solution 10 7 cfu / mL, and the colony growth of each group was observed after culturing at 37 °C for 24 h after different light exposure times. The mixed solution without photocatalytic drugs was used as the blank control group. Figure 6As shown in the figure, under illumination conditions, the sterilization rates of pure TiO2 and pure Ti-MOF are only 14.3% and 2.7%, indicating that pure Ti-MOF material has almost no sterilization ability. Pure TiO2 is restricted by its wide bandgap and low photogenerated electron-hole utilization rate, and its photocatalytic sterilization efficiency is low. With the loaded nano-Ag particles as active sites, it can promote the adsorption and activation of O2, enrich electrons, and reduce the photogenerated electron-hole recombination rate. The sterilization efficiency of Ti-MOF@Ag / Ti-MOF composite material is significantly improved compared with pure TiO2 and pure Ti-MOF, reaching 59.6%. After forming a core-shell structure with TiO2 as the core, due to the reduction of the overall material impedance, the photogenerated electron-hole recombination rate and the more efficient use of light energy, the sterilization rate of TiO2@Ag / Ti-MOF composite material has been further improved compared with Ti-MOF@Ag / Ti-MOF composite material, reaching more than 99.99%. In summary, the prepared TiO2@Ag / Ti-MOF composite material still has considerable bactericidal ability at an extremely low bactericidal concentration (50 μg / mL), and the generation of active free radicals by photocatalysis under light conditions is the main reason for the bactericidal performance.

[0029] Example 2 1) Prepare 2-aminoterephthalic acid in N, N-dimethylimidazole (DMF) at a concentration of 0.3 mmol / mL as solution A; 2) dissolving tetrabutyl titanate in anhydrous methanol and mixing them evenly to obtain solution B; the volume ratio of tetrabutyl titanate to anhydrous methanol is 1:26; 3) Mix solution A and solution B according to the molar ratio of tetrabutyl titanate and 2-aminoterephthalic acid of 1:3; after mixing evenly, transfer to a microwave oven, set the microwave power to 600 W, set the heating time to 2 hours, and dry the precipitate to obtain Ti-MOF with Ti vacancies; 4) Disperse the Ti-MOF with Ti vacancies in a 2 mol / L silver ammonia solution, where the mass fraction of the Ti-MOF with Ti vacancies in the solution is 22%. Transfer the mixed solution to a sealed container, and fill the container with the solution to more than 2 / 3 of its volume; 5) React at 80 °C for 300 min to obtain Ti / vacancy-MOF@Ag / Ti-MOF structure; 6) The Ti-MOF@Ag / Ti-MOF was transferred to a tube furnace and heat treated at 300 °C in an air environment to obtain a TiO2@Ag / Ti-MOF structure.

[0030] The characterization results of this example are the same as those of Example 1, both of which are core-shell materials with TiO2 as the core and Ag-substituted Ti-MOF as the shell.

[0031] Example 3 1) Prepare 2-aminoterephthalic acid in N, N-dimethylimidazole (DMF) at a concentration of 0.2 mmol / mL as solution A; 2) dissolving tetrabutyl titanate in anhydrous methanol and mixing them evenly to obtain solution B; the volume ratio of the tetrabutyl titanate to anhydrous methanol is 1:28; 3) Solution A and solution B were mixed in a molar ratio of 1:5 between tetrabutyl titanate and 2-aminoterephthalic acid; after being evenly mixed, the mixture was transferred to a microwave oven, the microwave power was set to 600 W, the heating time was set to 2 hours, and the precipitate was dried to obtain a Ti-MOF with Ti vacancies; 4) Disperse the Ti-MOF with Ti vacancies in a 3 mol / L silver ammonia solution, where the mass fraction of the Ti-MOF with Ti vacancies in the solution is 30%. Transfer the mixed solution to a sealed container, and fill the container with the solution to more than 2 / 3 of its volume; 5) React at 80 °C for 260 min to obtain a Ti / vacancy-MOF@Ag / Ti-MOF structure; 6) The Ti-MOF@Ag / Ti-MOF was transferred to a tube furnace and heat treated at 250 °C in an air environment to obtain a TiO2@Ag / Ti-MOF structure.

[0032] The characterization results of this example are the same as those of Example 1, both of which are core-shell materials with TiO2 as the core and Ag-substituted Ti-MOF as the shell.

[0033] Example 4 1) Prepare 2-aminoterephthalic acid in N, N-dimethylimidazole (DMF) at a concentration of 0.3 mmol / mL as solution A; 2) dissolving tetrabutyl titanate in anhydrous methanol and mixing them evenly to obtain solution B; the volume ratio of the tetrabutyl titanate to anhydrous methanol is 1:25; 3) Solution A and solution B were mixed in a molar ratio of tetrabutyl titanate to 2-aminoterephthalic acid of 1:2.5; after being mixed evenly, the mixture was transferred to a microwave oven, the microwave power was set to 600 W, the heating time was set to 2 hours, and the precipitate was dried to obtain a Ti-MOF with Ti vacancies; 4) Disperse the Ti-MOF with Ti vacancies in a 1.5 mol / L silver ammonia solution, where the mass fraction of the Ti-MOF with Ti vacancies in the solution is 35%. Transfer the mixed solution to a sealed container, and fill the container with the solution to more than 2 / 3 of its volume; 5) React at 80 °C for 300 min to obtain Ti / vacancy-MOF@Ag / Ti-MOF structure; 6) The Ti-MOF@Ag / Ti-MOF was transferred to a tube furnace and heat treated at 300 °C in an air environment to obtain a TiO2@Ag / Ti-MOF structure.

[0034] The characterization results of this example are the same as those of Example 1, both of which are core-shell materials with TiO2 as the core and Ag-substituted Ti-MOF as the shell.

[0035] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. A TiO2@Ag / Ti-MOF functional material, characterized in that: The material has a core-shell structure, with the core being TiO2 and the shell being a silver-substituted Ti-MOF structure.

2. A method for preparing TiO2@Ag / Ti-MOF functional material, characterized in that: The steps include: (1) Preparation of Ti-MOF with Ti vacancies by microwave hydrothermal method; (2) Filling the Ti vacancies on the surface with silver ions to form a Ti vacancy-MOF@Ag / Ti-MOF structure; (3) The Ti-MOF@Ag / Ti-MOF structure is heated to form a TiO2@Ag / Ti-MOF structure.

3. The preparation method according to claim 2, characterized in that: The Ti-MOF with Ti vacancies is prepared by the following method: (1) Prepare 2-aminoterephthalic acid in N, N-dimethylimidazole at a concentration of 0.2-0.3 mmol / mL as solution A; (2) dissolving tetrabutyl titanate in anhydrous methanol and mixing them evenly to obtain a solution B; the volume ratio of the tetrabutyl titanate to anhydrous methanol is 1:(22-28); (3) Mix solution A and solution B in a molar ratio of tetrabutyl titanate to 2-aminoterephthalic acid of 1:(0.2-5); after mixing evenly, transfer to a microwave oven with a microwave power of 600 W for 2 h, and dry the precipitate to obtain a Ti-MOF with Ti vacancies.

4. The preparation method according to claim 2, characterized in that: The Ti vacancy-MOF@Ag / Ti-MOF structure is prepared by the following method: dispersing Ti-MOF with Ti vacancies in a silver ammonia solution, reacting at 80° C. for 240 to 300 minutes, and obtaining a Ti vacancy-MOF@Ag / Ti-MOF structure.

5. The preparation method according to claim 4, characterized in that: The concentration of the silver ammonia solution is 1-3 mol / L; the mass fraction of the Ti-MOF with Ti vacancies in the solution is 14-35%.

6. The preparation method according to claim 2, characterized in that: The heating method in step 3 is heat treatment at 200-300° C. in a tubular furnace in an air environment.

Citation Information

Patent Citations

  • Preparation method and application method of titanium dioxide nanosheet supported MIL-100 (Fe) composite photocatalysis material

    CN106238100A

  • Multi-shell nanoparticle TiO2 photocatalyst as well as preparation method and application thereof

    CN107497428A

  • Ti-MOFs (Metal-Organic Frameworks) material synthesized by solvothermal method, and preparation method thereof

    CN109880114A

  • Preparation method of silver-metal organic framework composite antibacterial material

    CN111109293A

  • Ag-MoS2@TiO2 nano photocatalytic sterilization material and preparation method thereof

    CN111418608A

Cited By

  • Silver monatomic antibacterial and antiviral material as well as preparation method and application thereof

    CN121195972A